AMBIENTE E ESPAÇO NA EDUCAÇÃO INFANTIL: CONCEPÇÃO NOS DOCUMENTOS OFICIAIS - Zenilde Durli; Marizete Rossana Aparecida Brasil (Universidade do Oeste de Santa Catarina, 2012)
The paper presents a study on the issue of pedagogical space in children's education.The analysis focuses on the Subsidies for Registration and Operation of Institutionsof Children's Education - Volume II 1998, the Curricular References for Children'sEducation 1998, and the Basic Parameters of Infrastructure for Children's EducationInstitutions 2006 that comprise the documental corpus of research. The objective isto understand, by means of content analysis, the concept of space/physical space andenvironment/physical environment in these official publications related to education.The survey results show that in official documents the concepts of space andenvironment are treated as synonyms, contrary to theoretical treatises on the subjectand complicating the understanding that the teacher should have on the specifics ofeach practice developed in the children's educational institutions.